Ekspresi Ideologi Keagamaan: Menyelami Kontroversi Politik Identitas di Indonesia - Dedi Susanto; Muhammad Amri Tajudin; Abdullah Thalib (CBJIS: Cross-Border Journal of Islamic Studies, 2024)
The contestation of religious ideology in identity politics in Indonesia has become a significant social phenomenon, affecting the dynamics of politics and inter-religious relations in this pluralistic country. This article aims to analyze the role of religious ideology in identity politics and its impact on social life in Indonesia. This study uses a qualitative approach with literature analysis and case studies, such as the 2017 Jakarta gubernatorial election, to illustrate how religion is politicized to gain political support. The results show that religious-based identity politics is increasingly dominant in the public sphere, exacerbating social polarization among religious communities, and increasing discrimination against religious minority groups. Social media plays a significant role in accelerating the spread of religious ideology, while the state, through the Pancasila policy, seeks to maintain social harmony amidst differences. This article concludes that although the contestation of religious ideology can exacerbate social tensions, inter-religious dialogue and increasing social tolerance can be the key to reducing these negative impacts and maintaining unity in diversity in Indonesia.